IMPLEMENTASI INTEGRASI PEMBELAJARAN IPA DENGAN AL QURAN DI SMP AL-AMJAD KOTA MEDAN - Achyar Zein; Edi Saputra; Nanda Felani Baihaqi (JP : JURNAL PENDIDIKAN, 2021)
Abstract: This research aims to reveal how the imple-mentation of the integration of IPA learning with Al Quran which for several years has been imple-mented. This type of research is a qualitative study with a descriptive approach of research that seeks to describe the incident in the field as it is. In collecting data used various techniques such as interviews, observation or documentation. The primary source in this research is the teacher of science study. The results of this study concluded that the integration of IPA with Al Quran is an educational approach that combines general educa-tion with the evidence of the Koran. The align-ment emphasizes foster pattern, material alignment and sphere alignment. There is no regional dichotomy of separation between general science and religion (the evidence of the Qur'an). With this approach the learning activities are not detached from the doctrinal frame of Islamic values. As supporting the implemen-tation of the integration is supported by the concept of curriculum 2013 and using a special curriculum that is the development of the school curriculum, which its development will expand the aspect of life skill so it has the same portion as the general subjects. The concept of integration implemented in junior high school Al Amjad Medan is oriented to form the mindset, personality and character of learners who are in accordance with Islamic values.Keywords: Integration Learning, IPA, Qur’an